Axon initial segments: diverse and dynamic neuronal compartments - Yoshimura, Takeshi (2014)
The axon initial segment (AIS) is a structurally and molecularly unique neuronal compartment of the proximal axon that functions as both a physiological and physical bridge between the somatodendritic and axonal domains. The AIS has two main functions: to initiate action potentials and to maintain neuronal polarity. The cytoskeletal scaffold ankyrinG is responsible for these functions and clusters ion channels at the AIS. Recent studies reveal how the AIS forms and remarkable diversity in its structure, function, and composition that may be modulated by neuronal activity and post-translational modifications of AIS proteins. Furthermore, AIS proteins have been implicated in a variety of human diseases. Here, we discuss these findings and what they teach us about the dynamic AIS.